2016
DOI: 10.1111/jocn.13133
|View full text |Cite
|
Sign up to set email alerts
|

Is there a difference between the STOPBANG and the Berlin Obstructive Sleep Apnoea Syndrome questionnaires for determining respiratory complications during the perioperative period?

Abstract: Questionnaires may be used to determine the risk of obstructive sleep apnoea syndrome, which could impact the anaesthetisation of surgical patients. Questionnaires for determining the risk of obstructive sleep apnoea syndrome should be used regularly for surgical patients, and these questionnaires should be used to improve clinical protocols for anaesthesia and postanaesthesia care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Among the included studies, 5 were retrospective 24 , 25 , 27 , 35 , 36 and 11 were prospective controlled studies. 26 , 28 34 , 37 – 39 Ten studies confirmed OSA by overnight polysomnography 24 , 25 , 27 , 29 , 35 or electronic database entries, 28 , 30 , 31 , 34 , 37 3 used the STOP-Bang screening questionnaire, 33 , 38 , 39 2 identified patients by clinical diagnosis, 26 , 36 and 1 used both polysomnography and the STOP-Bang questionnaire. 32 …”
Section: Difficult Airway and Osamentioning
confidence: 99%
See 3 more Smart Citations
“…Among the included studies, 5 were retrospective 24 , 25 , 27 , 35 , 36 and 11 were prospective controlled studies. 26 , 28 34 , 37 – 39 Ten studies confirmed OSA by overnight polysomnography 24 , 25 , 27 , 29 , 35 or electronic database entries, 28 , 30 , 31 , 34 , 37 3 used the STOP-Bang screening questionnaire, 33 , 38 , 39 2 identified patients by clinical diagnosis, 26 , 36 and 1 used both polysomnography and the STOP-Bang questionnaire. 32 …”
Section: Difficult Airway and Osamentioning
confidence: 99%
“…Of those patients, 32,052 had OSA (identified by polysomnography, electronic database, chart or clinical diagnoses, and STOP-Bang questionnaires) and 234,551 did not. In summary, 12 studies reported on difficult intubation, 24 29 , 31 – 33 , 35 , 38 , 39 6 on difficult mask ventilation, 28 , 30 , 31 , 36 , 38 , 39 2 on both difficult intubation and mask ventilation, 28 , 37 and 2 on failed supraglottic airway. 27 , 34 Several studies reported >1 difficult airway outcome.…”
Section: Difficult Airway and Osamentioning
confidence: 99%
See 2 more Smart Citations
“…Each of these factors might be associated with increased postoperative stay, regardless of the presence or absence of OSA. Disentangling these contributors to sleep apnea from the disease itself, therefore, is challenging [23]. Finally, the discovery of an early discharge in LR patients despite short procedure duration in an outpatient setting further demonstrates the potential robustness of the STOP-BANG questionnaire.…”
Section: Discussionmentioning
confidence: 99%